Aspirations, Apprehensions and the Availability of Career Guidance among Dental Interns in Kerala, India - PS Sajitha; Susan Thomas; Vivek Narayan (Indian Journal of Dental Research)
Background: Dental graduates undergo stress owing to factors such as academic pressure and job uncertainty. Additionally, a lack of guidance with regard to clinical entrepreneurship is a cause of great concern. This study aimed to assess the aspirations and apprehensions of dental interns and to determine the availability of career guidance among them. Materials and Methods: A cross-sectional online survey was conducted using a self-designed electronic questionnaire. A total of 480 dental interns from both public and private dental institutions in the state of Kerala were included in this study. The stratified random sampling method was adopted, and the population proportion ratio was used to collect the samples. Data were analysed using the Chi-square test, Student's t-test, analysis of variance and multivariate linear regression. Results: The majority of the interns were females (87.5%); 75% of the participants had graduated from private institutions and 44% resided in rural areas. The apprehension score was high among interns from private institutions and those who belonged to a higher socioeconomic stratum (P < 0.05). However, the level was low among those who expressed strong aspirations (r = -0.213) and satisfaction (r = -0.329). Conclusion: The determinants for apprehension exhibited substantial disparities among the private and public educational sectors. Although the scenario of students who approached dentistry was similar, their plans for the future differed based on gender, sector and socioeconomic status. The lack of effective career guidance from institutions might impact the advancement of dentistry in future.